STRESS AMONG FEMALE TEACHERS IN HYDERABAD SINDH PAKISTAN - Kazi, Shazia; GhafoorKazi , Abdul; Subhan Kazi, Abdul; Rashid Ali Ahmed Ali Ahmed Mohamed Al Ali (International Journal of Psychosocial Rehabilitation, 2020)
Many studies have been conducted to understand problems experienced by working women and most of them indicate that working women suffer from psychological and physical ailments due to stress caused by the struggle to balance both domains of life i.e. work and family. This study examines the level of stress (anger, anxiety, mania and depression) in female teachers of Pakistan. Using multistage cluster sampling technique total 280femaleteachers from nine public higher secondary schools of district Hyderabad, Sindh, Pakistan were chosen as the respondents for this study. Based on related stress theories, four dimensions of stress were determined. Across-sectional survey was carried out and data were collected using self-administered survey. The results of the descriptive analysis indicate that, in general, the female teachers experienced high level of stress in their workplace. With regard to the stress dimensions, the respondents were found to experience high level of anger, anxiety, mania and depression.